Effects of SDG vegetables gardening on ukhuwwah and ta’awun among higher education communities of practice - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi (2020)
This study explores the effect of Sustainable Development Goals (SDG) vegetables gardening on Ukhuwwah and Ta’awun among communities of practice in higher education institutions. In higher education context, Ukhuwwah (bonding) and Ta’awun (mutual cooperation) are essential to sustain teamwork and collaboration among the communities of practice. Communities of practice (COP) refer to the dynamic interactions among staff of higher education. The study uses naturalistic observation method understands the effect of SDG vegetables gardening activities on Ukhuwwah and Ta’awun among communities of practice. The results suggest that socialization with solid purpose are easily bringing people to get together to achieve common outcomes.